Maximizing Student Research Engagement: Weighing the Impact of Institutional Support on Perceived Gains and Motivation - Lőrincz, Marianna; Povidaichyk, Mykhailo (Journal of Teaching and Learning, 2026)
Despite its recognition as a high-impact practice, including student research in curricula per se does not guarantee meaningful research experiences or academic gains. Therefore, this study explored how the quality of institutional support affected students’ perceptions of gains and motivation associated with research. Using bivariate correlational analyses, ordinal logistic regression, and mediation analyses on self-reported data from 212 university students, evidence of the relationship between institutional support and research outcomes was obtained. Notably, the findings revealed a strong positive correlation between the research experiences offered and self-assessed gains in research skills and motivation. The gain ratings progressed proportionately to the evaluation of research experiences. Institutional support emerged as a key predictor of research skills mediated by motivation. While institutional type and academic achievement were not significantly associated with research skills ratings, students from teacher education institutions scored lower on perceived gains. In all, the findings underscore the importance of providing students with high-quality, accessible research experiences to enhance their academic and professional development.